2005
DOI: 10.2349/biij.1.1.e4
|View full text |Cite
|
Sign up to set email alerts
|

Phytobezoar: an unusual cause of intestinal obstruction

Abstract: Small bowel phytobezoars are rare and almost always obstructive. There have been previously reported cases of phytobezoars in the literature, however there are few reports on radiological findings for small bowel bezoars. Barium studies characteristically show an intraluminal filling defect of variable size that is not fixed to the bowel wall with barium filling the interstices giving a mottled appearance. On CT scan, the presence of a round or ovoid intraluminal mass with a ‘mottled gas’ pattern is believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 5 publications
(6 reference statements)
1
36
0
1
Order By: Relevance
“…With patients of no history of gastric surgery, diabetic gastroparesis, vegetarian diet, hypothyroidism or edentulousness could be the other predisposing factors. [2][3][4][5][6][7] Our patient had none of these factors. However, out patient's history revealed that there was an excessive consumption of persimmon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With patients of no history of gastric surgery, diabetic gastroparesis, vegetarian diet, hypothyroidism or edentulousness could be the other predisposing factors. [2][3][4][5][6][7] Our patient had none of these factors. However, out patient's history revealed that there was an excessive consumption of persimmon.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms such as abdominal pain, vomiting or dyspepsia are the common presenting symptoms assisting in locating the bezoars. [2][3][4][5][6][7] Radiologically, plain X-ray graphics are not diagnostic otherwise showing air-fluid levels. However, series of X-ray graphics may be helpful in the follow-up of possible obstruction due to fragmented bezoars in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3 The most common CT finding of bezoars includes a round or ovoid intraluminal mass that contains mottled gas at the obstructed site. 1,15 However, abdominal CT may fail to detect small bowel bezoars, as it can be interpreted as normal intraluminal food materials. To properly manage small bowel obstruction caused by bezoars, early surgical treatment is essential, 3 and delayed treatment may significantly increase complications and mortality.…”
Section: 홍인택 등 알로에 베라 위석에 의한 소장 폐색 증례 보고mentioning
confidence: 99%
“…Small bowel obstruction due to bezoars is clinically uncommon, accounting for approximately 2-4% of all obstructions. [1][2][3] Bezoars are solidified substances formed by a mixture of indigestible exogenous substances with other substances in the gastrointestinal tract. Bezoars are usually formed in the stomach and passed down into the small bowel, resulting in small bowel obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Patient symptoms improved drastically in the following days. Phytobezoars, the most common type of bezoar, are concretions of poorly digested fruit and vegetable fibers that are found in the alimentary tract [1,2]. A number of surgical, endoscopic, and pharmacological treatments with variable efficacy have been proposed [3,4].…”
mentioning
confidence: 99%